Pronominal Affix of Bugic Language Enjoyable Dialec - Abd. Rahman Rahim (Eduvest - Journal of Universal Studies, 2022)
In terms of social strata, the same language has different variations if it is spoken by groups of people with lower-middle social strata and upper-middle social strata. This study aims to describe the variation of Bugis pronominal affixes in the Ennak dialect used by Bugis speakers in Sinjai Regency. This research is classified into the type of qualitative descriptive research. The data in this study are the speeches of the Bugis people in Sinjai Regency or the Ennak dialect. Data collection was carried out by speaking and tapping techniques. This study uses intralingual equivalent data analysis. Data that is compared with intralingual equivalents are differences and similarities which have other names, namely HBS (Same Comparative Relations) and HBB (Different Comparative Relations), both of which are advanced techniques in data analysis. The results showed that the use of Bugis pronominal affixes in the Ennak dialect consisted of proclitic and enclitic. has a different style from the use of the clitic form in Indonesia.